An audit of the decision to delivery interval in emergency caesarean section and its effect on neonatal outcome - G., Anuradha; V., Nirupama; George, Shirley (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Emergency caesarean section (CS) is divided into four categories based on the degree of urgency by RCOG and NICE guidelines. It is recommended that the decision to delivery interval (DDI) in emergency CS should be within 30 minutes in category 1 and within 75 minutes in category 2. Our Primary objective was to study the incidence and indications of emergency CS and audit the DDI in emergency CS at tertiary care hospital. Our secondary objective was to study the effect of DDI on neonatal outcome. Methods: Descriptive study was carried out among 409 women who underwent emergency CS from August 2018 to December 2018 at St. John's medical college hospital, Bangalore. Relevant data was collected by chart review. Emergency CS were categorised according to RCOG guidelines based on the degree of urgency and further classified based on DDI as <30 minutes, 30-75 minutes and >75 minutes. Results: We had 409 cases of emergency CS. Category 1 had 113 (27.63%) cases, category 2 had 126 (30.81%) cases and category 3 had 170 (41.56%) cases. DDI of <30 minutes was achieved in 19.5% in category 1, DDI of <75 minutes was achieved in 93.65% in category 2. Fetal distress was the leading cause of emergency CS in category 1 and 2. There was a high incidence of low APGAR in babies delivered in <30 minutes and lower APGAR was significantly associated with <30 minutes of DDI (p<0.0001). Conclusions: Fetal distress was the leading cause of emergency CS. DDI interval of <30 minutes was not always associated with good neonatal outcome; Category of CS has a significant effect on neonatal outcome.